Current status and future prospects of protein vaccine candidates against Schistosoma mansoni infection - Tahir Eyayu (Parasite Epidemiology and Control, 2020)
Schistosomiasis is an acute and chronic tropical parasitic disease caused by blood dwelling worm of the genus Schistosoma. It is the most destructive disease globally and is a major cause of morbidity and mortality for developing countries. Three main species of schistosomes infect human beings from which S. mansoni is the most common and widespread. Over the last several decades, chemotherapy using praziquantel has been a commonly used strategy for the treatment and control of schistosomiasis. However, control programs focused exclusively on chemotherapy have been challenging because of the frequency and rapidity of reinfection and these programs were expensive. Thus, new schistosomiasis control strategies will be needed.Vaccination strategy would be an ideal tool for a significant and sustainable reduction in the transmission and disease burden of schistosomiasis. An effective anti schistosome vaccine would greatly contribute to decreasing schistosomiasis-associated morbidity via protective immune responses leading to reduced worm burdens and decreased egg production. Vaccine development is a long process that can take decades. There have been three candidate vaccines that have been produced by Good Manufacturing Procedure and entered human clinical trials for S. mansoni are Sm14, SmTSP-2, and Sm-p80. Other candidates that are in pre-clinical trials at various stages include paramyosin, Sm29, SmKI-1, and Sm23. Since the growth of several new technologies, including genomics, transcriptomics, microarrays, immunomic profiling, and proteomics, have helped in the identification of promising new target schistosome antigens. Therefore, this review considers the present status of protein vaccine candidates against Schistosoma mansoni and provides some insight on prospects vaccine design and discovery.